The evaluation of extracorporeal shock wave therapy on collagenase induced superficial digital flexor tendonitis - Kersh, K. D.; McClure, S. R.; Van Sickle, D.; Evans, R. B. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Extracorporeal shock wave therapy (ESWT) is being used to treat desmitis and tendonitis in horses. This paper compares the clinical, ultrasonographic and histological characteristics of ESWT treated collagenase induced superficial digital flexor tendon (SDFT) lesions, versus untreated controls. This blinded study utilizes six mature, healthy horses where bilateral forelimb SDFT lesions were induced. One forelimb was treated while the other served as an untreated control. Three shock wave treatments were administered at three week intervals. At weekly intervals, ultrasonograms were used to measure: 1) percentage lesion at the maximum injury zone (MIZ), 2) the grey scale of the SDFT at the MIZ, 3) the percentage disruption of the longitudinal fibres at the MIZ. The data were also summed from 8–20 cm distal to the accessory carpal bone. Measurements of the external width of the SDFT were obtained through the study period. Examinations were performed on four occasions to evaluate heat, response to palpation, presence/character of swelling over the SDFT, and lameness. At the completion of the study all tendons were evaluated histologicalally. The lesion size, grey scale, and longitudinal fibre disruption at the MIZ, and sum of each variable changed significantly over time, however, there was no difference between treated and control groups. Histopathology showed increased neovascularization in treated tendons (p = 0.001). When compared to untreated controls, ESWT did not change the ultrasonographic appearance of the tendons. However, it did increase neovascularization.
Keywords: Superficial digital flexor tendons; tendonitis; extracorporeal shock wave therapy; collagenase induced lesions